Analisis Sistem Informasi Akuntansi Penerimaan Kas Pada Klinik Al-Khoir Mananti Kabupaten Padang Lawas Sumatera Utara - Hasibuan, Mardiah Khofifah; Nawawi, Zuhrinal; Syafina, Laylan (Journal of Student Development Informatics Management (JoSDIM), 2023)
The Cash Receipts Accounting Information System is a unit for collecting and recording transactions that can help leaders to handle company receipts. The aim of this research is to determine the Cash Receipt Accounting Information System at the Al-Khoir Mananti Clinic, Padang Lawas Regency, North Sumatra. This type of research is qualitative research which is descriptive in nature. Data collection techniques were carried out through interviews and documentation. The results of this research indicate that the implementation of the cash receipts accounting information system at the Al-Khoir Mananti Padang Lawas Clinic is in accordance with the accounting information system and can be said to be good. However, despite this, there are still shortcomings in terms of the system which is still manual in some parts, namely in the clinic records in the patient registration section, notes are still handwritten by the clinic cashier. Because the manual system is carried out by humans, there is a greater percentage of errors compared to recording. The internal control system at the Al-Khoir Mananti Padang Lawas Clinic is inadequate.